From the phenomenological solution to McTaggart’s paradox to the problem of pluralism in the description of temporal reality - Cormick, Claudio (Contrastes. Revista Internacional de Filosofía, 2017)
In this paper we attempt to continue the proposal of a solution to McTaggart’s paradox on the basis of a return to a line of analysis traceable back to Dummett, and its implementation with certain tenets of Merleau-Pontyan phenomenology. With this aim, we have to deepen the positions of the author of Truth and other enigmas which point towards an objection against one “complete description” of reality and favour, on the contrary, a plurality of “maximal descriptions”. Our attempt must not, however, adopt a “pluralism” which can be targeted by Nicholas Smith’s objections, to whom, in turn, we reply by turning to the phenomenological notion of “synthesis of transition”. We conclude that the “pluralism” of temporal descriptions that allows us to escape from McTaggart’s paradox is not incompatible with the requisite of “compossibility” laid out by Smith.